Two new species of Philosepedon Eaton (Diptera: Psychodidae: Psychodinae) from the Atlantic Coastal Rain Forest of northeastern Brazil - Bravo, Freddy; Chagas, Cinthia; Cordeiro, Danilo (Zootaxa, 2006)
Two new Brazilian species of Philosepedon Eaton from wet forests of the Atlantic Coastal Rain Forest of Bahia, northeastern Brazil, are described and illustrated. These two new species are morphologically similar and are probably related. They can be distinguished from other species of Philosepedon by the presence of 13 flagellomeres with the 11 th and 12 th fused, the oval apical enlargement of R 2 and M 3 , an incomplete M 2 , and two tenacula on the cercus.